Research Methods in Public Administration and Public Management: An Introduction, 1st Edition - Thiel, Sandra van (Routledge, 2020)
Research in public administration and public management has distinctive features that influence the choices and application of research methods. Periods of change and upheaval in the public sector provide ample opportunities and cases for research, but the standard methodologies for researching in the social sciences can be difficult to follow in the complex world of the public sector. In a dynamic political environment, the focus lies on solving social problems whilst also using methodological principles needed for doing scientifically sound research.